A09 Health and economic benefits of active transport policies in Barcelona. Issue 2 (June 2015) - Pérez, Katherine; Olabarria, Marta; Santamariña-Rubio, Elena; Nieuwenhuijsen, Mark; Rojas-Rueda, David
Abstract: Background: Since the first Road Safety Plan was approved in Barcelona in 2000, other plans followed and were integrated into the overall mobility plans of the city. Actions stimulating active transportation included increasing pedestrian priority areas, implementation of zones 30, audits of crosswalks, bike lanes, public bicycle program, reduction of car use by limiting parking for residents, increasing public transport, etc. This paper aims to estimate the health and economic benefits of these policies that promoted walking and cycling. Methods: We conducted a pre-post evaluation study, comparing walking and cycling trips in 2009 to 2013. We used the HEAT (Health Economic Assessment Tool) developed by WHO. The study population are persons older than 14 who made a trip walking or cycling in Barcelona city during the period of study. Data on the number of trips walking or cycling and the duration of the trips were obtained from the annual daily travel survey carried out in Barcelona (EMEF). It collects information on all trips carried out on the previous working day. We used the value of statistical life provided by HEAT for Spain: 3.203.000€. We estimated the number of deaths per year that were prevented due to changes in the level of walking and cycling from 2009 to 2013 and the economic benefit resulting from prevented deaths. Results: The number of people reporting walking for travel increased from 783, 518 in 2009 to 862, 021 in 2013: This gives an increase in average daily time spent walking per person from 47.5 min to 49.6 min per day. Taking this into account, 86.1 deaths per year are prevented by this change in walking. The current value of the average annual benefit averaged across 5 years of this level of walking is: 47.355 million €. The number of people reporting cycling for travel the day before increased from 40, 430 in 2009 to 60, 274 in 2013: The average daily time spent cycling per person was 51, 8 min in 2009 and 49, 8 min in 2013. Taking this into account, 8, 2 deaths per year are prevented by this change in cycling. The current value of the average annual benefit averaged across 5 years of this level of cycling is: 4.492 million €. Conclusions: Changes in transport policies in Barcelona city, which promoted active transportation, produced a clear impact on health benefits related to physical activity.